2012
DOI: 10.5194/bg-9-2781-2012
|View full text |Cite
|
Sign up to set email alerts
|

The stoichiometry of inorganic carbon and nutrient removal in the Mississippi River plume and adjacent continental shelf

Abstract: Abstract. The stoichiometry of dissolved inorganic carbon (DIC) and nutrients during biological uptake is widely assumed to follow the Redfield ratios (especially the C / N ratio) in large river plume ecosystems. However, this assumption has not been systematically examined and documented, because DIC and nutrients are rarely studied simultaneously in river plume areas and interpretation of ratios can be confounded by strong river-ocean mixing as well as intense biological activity. We examined stoichiometric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 53 publications
(73 reference statements)
6
40
1
Order By: Relevance
“…7.6), whereas such overall removal is apparent in the Mississippi plume (Fig. 7.5) (Cai 2003;Guo et al 2012;Huang et al 2012), in the Pearl River plume (Cai et al 2004;Dai et al 2008), and the Changjiang plume (Wang et al 2000;Chou et al 2009b).…”
Section: Co 2 In the Amazon River Plumementioning
confidence: 94%
See 2 more Smart Citations
“…7.6), whereas such overall removal is apparent in the Mississippi plume (Fig. 7.5) (Cai 2003;Guo et al 2012;Huang et al 2012), in the Pearl River plume (Cai et al 2004;Dai et al 2008), and the Changjiang plume (Wang et al 2000;Chou et al 2009b).…”
Section: Co 2 In the Amazon River Plumementioning
confidence: 94%
“…Other factors also matter. For example, the Mississippi River has lower turbidity than the Changjiang River, and thus high biological production and CO 2 removal in the plume has occurred at low salinity zone of 20 to 30 or occasionally even at salinity as low as 12 (Dagg et al 2008;Huang et al 2012) in the Mississippi plume, whereas in the Changjiang plume, biological bloom rarely has occurred at salinity less than 28. Figure 7.6.…”
Section: Co 2 In the Mississippi River Plumementioning
confidence: 99%
See 1 more Smart Citation
“…We also took advantage of extensive in situ observations (shipboard CTD casts and Niskin bottle samplings) collected during research cruises in the northern GoM spanning over the period of 2005-2010 (Data were collected from different sources, including the Environmental Protection Agency; Lehrter et al, 2009Lehrter et al, , 2012Lohrenz et al, 2008;Cai et al, 2011;Huang et al, 2012; Louisiana Universities Marine Consortium; Rabalais et al, 2007; Mechanisms Controlling Hypoxia (MCH) Project; Southeast Monitoring and Assessment Program (SEAMAP); the NSF-funded GulfCarbon Project and Mississippi-Atchafalaya-Gulf of Mexico Mixing Experiment (MMAGMIX)). Together, there are more than 8000 surface observations of water temperature, salin- ity, NO 3 , NH 4 , and chlorophyll concentrations.…”
Section: Model-data Comparisonsmentioning
confidence: 99%
“…Within the Mississippi River plume, Cai (2003) observed that DIC losses occurred where salinity was , 30 and noted the cause might be a combination of biological production and CaCO 3 precipitation. Guo et al (2012) and Huang et al (2012) subsequently concluded that biological production was the main cause for the plume DIC removal and the effect of CaCO 3 precipitation was minor.…”
mentioning
confidence: 99%